Exploring hydrodynamic cavitation for citrus waste valorisation in Malta: from beverage enhancement to potato sprouting suppression and water remediation - Psakis, Georgios; Lia, Frederick; Valdramidis, Vasilis P.; Gatt, Ruben (Frontiers in Chemistry, 2024)
Introduction: The endorsement of circular economy, zero-waste, and sustainable development by the EU and UN has promoted non-thermal technologies in agro-food and health industries. While northern European countries rapidly integrate these technologies, their implementation in Mediterranean food-supply chains remains uncertain. Aims: We evaluated the usefulness of hydrodynamic cavitation (HC) for valorizing orange peel waste in the fresh orange juice supply chain of the Maltese Islands. Method: We assessed: a) the effectiveness of HC in extracting bioactive compounds from orange peels (Citrus sinensis) in water (35°C) and 70% (v/v) ethanol (−10°C) over time, compared to conventional maceration, and b) the potato sprouting-suppression and biosorbent potential of the processed peel for copper, nitrate, and nitrite binding. Results: Prolonged HC-assisted extractions in water (high cavitation numbers), damaged and/or oxidized bioactive compounds, with flavonoids and ascorbic acid being more sensitive, whereas cold ethanolic extractions preserved the compounds involved in radical scavenging. HC-processing adequately modified the peel, enabling its use as a potato suppressant and biosorbent for copper, nitrate, and nitrite. Conclusion: Coupling HC-assisted bioactive compound extractions with using leftover peel for potato-sprouting prevention and as biosorbent for water pollutant removal offers a straightforward approach to promoting circular economic practices and sustainable agriculture in Malta.